1999
DOI: 10.1093/ije/28.4.717
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma, aspirin intolerance, nasal polyposis and chronic obstructive pulmonary disease in a population-based study

Abstract: The current prevalence of doctor-diagnosed asthma among adults is 4.4%, and allergic rhinitis, nasal polyposis and aspirin intolerance are associated with an increased risk of asthma. There is also association between aspirin-induced asthma and allergic-like rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
301
3
14

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(341 citation statements)
references
References 27 publications
23
301
3
14
Order By: Relevance
“…The incidence of aspirin-intolerant syndrome is about 10% of the US population, with most NSAIDs showing some level of cross-reactivity [57,58]. COX-2 inhibitors also cross-react with aspirin with a much lower incidence and the order of crossreactivity appears to vary inversely with the [90].…”
Section: Pulmonarymentioning
confidence: 99%
“…The incidence of aspirin-intolerant syndrome is about 10% of the US population, with most NSAIDs showing some level of cross-reactivity [57,58]. COX-2 inhibitors also cross-react with aspirin with a much lower incidence and the order of crossreactivity appears to vary inversely with the [90].…”
Section: Pulmonarymentioning
confidence: 99%
“…Un estudio finlandés estudió la prevalencia de IA en cuatro mil trescientos adultos utilizando un cuestionario específico. En este estudio se describe una prevalencia general de 5,7%, mientras que la prevalencia de IA que se presenta con síntomas respiratorios fue de 1,2% 6 . La prevalencia de AIA en la población general es de aproximadamente 0,2%, pero en los pacientes con IA aumenta a 16,4% 3 .…”
Section: Epidemiologíaunclassified
“…Nasal symptoms are less commonly seen in children afflicted with AIA. In a Finnish study the prevalence of AIA was found to be only 1.2% and the overall aspirin intolerance was 5.7% 5 Life threatening attacks of asthma may be precipitated by a small amount of aspirin. This review discusses the current concepts in our understanding of AIA.…”
Section: Introductionmentioning
confidence: 96%